Tax Policy in the COVID-19 Crisis - Sebastian Eichfelder; Jonathan Hoke (Wirtschaftsdienst)
Abstract Current reform proposals call for a reduction of the corporate tax burden in Germany and justify this due to the competitiveness of Germany as a business location. However, in view of Germany’s continuously high attractiveness in this regard, these demands appear to be inappropriate, even in an international context. To ensure this attractiveness in the long term, it seems to be more important to focus on investments in digitisation, the digital infrastructure, and electromobility. Even in times of economic problems, e.g., the COVID19 pandemic, lowering the nominal tax burdens on companies is not necessarily the answer. Instead, temporary tax breaks for companies that invest during this phase of economic weakness may be more appropriate.